2020
DOI: 10.1002/chem.202001947
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Coupling Reactions: A New Concept for the Formation of Hexahydroxybenzene

Abstract: For linear and cyclic coupling reactions of CO, among other products, the formation of the hexapotassium salt of hexahydroxybenzene is of particularinteresting. The interaction of metallic potassium and CO offers, via the assumed K[OCCO]K as the result of severalc arbon monoxide coupling reactions, the formation of C 6 (OK) 6 among otherp roducts.T od ate, only speculations exist about the reaction pathway for these products,w hich were first described by Liebig in 1834. An ovel concept is suggested here, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…According to DFT calculations, the processes for loss of H 2 from the Ti IV ‐H intermediates and the formation of the Ti III ‐Cr dimer are exergonic. It is somewhat surprising that there was no coupling of CO, as had been observed, for example, by Berry and Bercaw for a bimetallic Zr−Fe complex [13b] or as it was discussed for other reactions of CO [13c,d] . The same reaction type was described for Cp* 2 Ti(η 2 ‐Me 3 SiC 2 SiMe 3 ) and CpCr(CO) 3 H (Scheme 12).…”
Section: Substitution Of Me3sic2sime3 By Substrates Coupling Reactions and Investigations Of The Obtained New Productssupporting
confidence: 53%
“…According to DFT calculations, the processes for loss of H 2 from the Ti IV ‐H intermediates and the formation of the Ti III ‐Cr dimer are exergonic. It is somewhat surprising that there was no coupling of CO, as had been observed, for example, by Berry and Bercaw for a bimetallic Zr−Fe complex [13b] or as it was discussed for other reactions of CO [13c,d] . The same reaction type was described for Cp* 2 Ti(η 2 ‐Me 3 SiC 2 SiMe 3 ) and CpCr(CO) 3 H (Scheme 12).…”
Section: Substitution Of Me3sic2sime3 By Substrates Coupling Reactions and Investigations Of The Obtained New Productssupporting
confidence: 53%
“…One of the first reports in this field came from Justus von Liebig, who in 1834 showed that the twophase reaction between molten potassium and CO gas generated a dark solid, "potassium carbonyl" (KCO) n . [1] This curious reaction was further investigated over the following century, [2] but it was not until the 1960s that Büchner and Weiss showed that (KCO) n consisted of a mixture of products, including potassium ethynediolate, KOCCOK, and potassium benzenehexolate, K 6 C 6 O 6 . [3] The proportion of these two products in the mixture was found to be dependent upon the temperature at which the reduction was carried out.…”
mentioning
confidence: 99%
“…It has also been proposed that transition metal impurities in the potassium used for the reduction of CO could have promoted the formation of both products. [2] In recent decades there has been a resurgence of interest in reactions involving the reductive homologation of CO, and the mechanisms by which they operate. [4] This is perhaps not surprising, considering the relationship of such reactions to the Fischer-Tropsch (F-T) process.…”
mentioning
confidence: 99%
“…Carbon monoxide is a readily available industrial feedstock that acts as a C1 source. The exploitation of CO as a building block has a long history [1] . In the early 1800s, reductive coupling of CO molecules by molten potassium were shown to afford salts of [KCO] n .…”
Section: Methodsmentioning
confidence: 99%